HYPERCHOLESTEROLEMIA AS A CAUSATIVE RISK FACTOR FOR NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) - Abbasi, Sarwat; Saadia Sadiq,; Nadia Haleem,; Salma Shazia,; Sara Jadoon,; Muhammad Israr, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Increased serum Cholesterol level is a known risk factor for cardiovascular diseases. Derangements in serum Cholesterol levels will affect normal hepatic Cholesterol homeostasis resulting in hypercholesterolemia. Non-Alcoholic fatty liver disease (NAFLD) initially asymptomatic but can lead to cirrhosis and hepatocellular carcinoma from mild steatosis to non-alcoholic steatohepatitis. The objective of this study is to find out hypercholesterolemia as a causative risk factor in NAFLD patients. This will help to prevent the development and progression of the disease.